POLITICAL INCLUSIVENESS AND UNDER-REPRESENTATION OF WOMEN IN NIGERIAN POLITICS, 1999 – 2015 - NWAGWU, Ejikeme J (Socialscientia: Journal of Social Sciences and Humanities, 2019)
The study investigates the factors responsible for women underrepresentation in Nigerian politics, In the process it also highlights the role of women in good governance, communal conflict resolution missions and inter-group conflicts. Marxist-Feminism theory was adopted as the framework of analysis. The study hinged largely on survey research design. Questionnaire instrument was used to collect information from respondents while qualitative method of data collection was also employed in the generation of relevant data from secondary sources and to secure reliable results. The paper took advantage of both quantitative and qualitative methods in data analysis. The investigation reveals that socio-cultural barriers and economic deprivations factors are responsible for women underrepresentation in Nigerian politics.